2023
DOI: 10.3390/pharmaceutics15082119
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Absorption for Intranasal Delivery of Drugs Targeting the Central Nervous System Using Alkylsaccharide Permeation Enhancers

Abstract: Intranasal delivery of drugs offers several potential benefits related to ease of delivery, rapid onset, and patient experience, which may be of particular relevance to patients with central nervous system (CNS) conditions who experience acute events. Intranasal formulations must be adapted to address anatomical and physiological characteristics of the nasal cavity, including restricted dose volume, limited surface area, and barriers to mucosal absorption, in addition to constraints on the absorption window du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Exposure to a hypercapnic gas mixture has a drying effect on the nasal mucosa (Lynn Webster, personal observation) which may have blunted the effect of the nasal absorption enhancer, dodecylmaltoside (DDM), included in this formulation. 12 DDM increases the absorption of both small molecules and peptides by transiently opening tight junctions between cells in the nasal epithelium 34,35 and has been demonstrated to both increase the C max and dramatically reduce the T max of nalmefene. 36 Consistent with this hypothesis, the most prominent differences in the pharmacokinetic properties of nasal nalmefene between previous studies in healthy volunteers 12 and the current study were observed during the first 20 min post administration, while plasma concentrations at 60 and 120 min were similar (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to a hypercapnic gas mixture has a drying effect on the nasal mucosa (Lynn Webster, personal observation) which may have blunted the effect of the nasal absorption enhancer, dodecylmaltoside (DDM), included in this formulation. 12 DDM increases the absorption of both small molecules and peptides by transiently opening tight junctions between cells in the nasal epithelium 34,35 and has been demonstrated to both increase the C max and dramatically reduce the T max of nalmefene. 36 Consistent with this hypothesis, the most prominent differences in the pharmacokinetic properties of nasal nalmefene between previous studies in healthy volunteers 12 and the current study were observed during the first 20 min post administration, while plasma concentrations at 60 and 120 min were similar (Table 3).…”
Section: Discussionmentioning
confidence: 99%